A revised Asingle model to explain stem cell dynamics in the mouse male germline. Issue 2 (August 2017) - Lord, Tessa; Oatley, Jon M
Abstract : Spermatogonial stem cells (SSCs) and progenitor spermatogonia encompass the undifferentiated spermatogonial pool in mammalian testes. In rodents, this population is comprised of Asingle, Apaired and chains of 4–16 Aaligned spermatogonia. Although traditional models propose that the entire Asingle pool represents SSCs, and formation of an Apaired syncytium symbolizes irreversible entry to a progenitor state destined for differentiation; recent models have emerged that suggest that the Asingle pool is heterogeneous, and Apaired /Aaligned can fragment to produce new SSCs. In this review, we explore evidence from the literature for these differing models representing SSC dynamics, including the traditional 'Asingle ' and more recently formed 'fragmentation' models. Further, based on findings using a fluorescent reporter transgene ( eGfp ) that reflects expression of the SSC-specific transcription factor 'inhibitor of DNA binding 4' ( Id4 ), we propose a revised version of the traditional model in which SSCs are a subset of the Asingle population; the ID4-eGFP bright cells (SSCultimate ). From the SSCultimate pool, other Asingle and Apaired cohorts arise that are ID4-eGFP dim. Although the SSCultimate possess a transcriptome profile that reflects a self-renewing state, the transcriptome of the ID4-eGFP dim population resembles that of cells in transition (SSCtransitory) to a progenitor state. Accordingly, at the next mitotic division, these SSCtransitory are likely to join the progenitor pool and have lost stem cell capacity. This model supports the concept of a linear relationship between spermatogonial chain length and propensity for differentiation, while leaving open the possibility that the SSCtransitory (some Asingle and potentially some Apaired spermatogonia), may contribute to the self-renewing pool rather than transition to a progenitor state in response to perturbations of steady-state conditions.